A nomogram for predicting screw loosening after single-level posterior lumbar interbody fusion utilizing cortical bone trajectory screw: A minimum 2-year follow-up study - Zhang, Yiqi; Li, Yue; Hai, Yong; Guan, Li; Zhang, Xinuo; Pan, Aixing; Lu, Hongyi; Wu, Bingchao; Liu, Yuzeng (Frontiers in Surgery, 2022)
Purpose: To investigate the risk factors for screw loosening after single-level posterior lumbar interbody fusion (PLIF) utilizing cortical bone trajectory (CBT) screw and establish a nomogram for predicting screw loosening Methods: A total of 79 patients (316 screws) underwent single-level PLIF with CBT screw were included in the study. Preoperative, postoperative and final follow-up demographic data, surgical data and radiographic parameters were documented and analyzed to identify risk factors and a predictive nomogram was established for screw loosening. The nomogram was assessed through concordance index (C-index), calibration plot, decision curve analysis (DCA) and internal validation. Results: The incidence of screw loosening was 26.6% in 79 patients, and 11.4% in 316 screws. Multifactorial regression analysis confirmed that fixed to S1 (FS1, OR=3.82, 95%CI 1.12-12.71, P=0.029), coronal angle of the screw (CA, OR=1.07, 95%CI 1.01-1.14, P=0.039) and cortical bone contacted layers (CBCL, OR=0.17, 95%CI 0.10-0.29, P<0.001) were risk factors and incorporated in the nomogram for predicting screw loosening after single-level PLIF with CBT screw. The C-index of the nomogram was 0.877 (95%CI 0.818-0.936) which demonstrated good predictive accuracy. The Calibration plot indicated an acceptable calibration of the nomogram that also had a positive benefit guiding treatment decision. Conclusion: FS1, CA and CBCL are identified to be significant risk factors for screw loosening after single-level PLIF with CBT technique. The nomogram we have established can be used to predict screw loosening and contribute to surgical decision.